2023
DOI: 10.3389/ti.2023.10803
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Assessment of Intestinal Damage in Controlled Donation After Circulatory Death for Visceral Transplantation

Abstract: There is an urgent need to address the shortage of potential multivisceral grafts in order to reduce the average time in waiting list. Since donation after circulatory death (DCD) has been successfully employed for other solid organs, a thorough evaluation of the use of intestinal grafts from DCD is warranted. Here, we have generated a model of Maastricht III DCD in rodents, focusing on the viability of intestinal and multivisceral grafts at five (DCD5) and twenty (DCD20) minutes of cardiac arrest compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
2
0
1
Order By: Relevance
“…Hasta hace pocos meses el uso de injerto intestinal procedente de donante en asistolia estaba proscrito debido al falso paradigma de que la susceptibilidad a la isquemia hacía inviable la utilización en la clínica de estos órganos. La evidencia preclínica (16) y clínica (17) aportada recientemente ha demostrado que el injerto multivisceral procedente de asistolia con perfusión normotérmica puede utilizarse con seguridad en pacientes. No obstante, las indicaciones y limitaciones del empleo de estos órganos aun están por definir.…”
Section: Injerto Procedente De Donante En Asistoliaunclassified
“…Hasta hace pocos meses el uso de injerto intestinal procedente de donante en asistolia estaba proscrito debido al falso paradigma de que la susceptibilidad a la isquemia hacía inviable la utilización en la clínica de estos órganos. La evidencia preclínica (16) y clínica (17) aportada recientemente ha demostrado que el injerto multivisceral procedente de asistolia con perfusión normotérmica puede utilizarse con seguridad en pacientes. No obstante, las indicaciones y limitaciones del empleo de estos órganos aun están por definir.…”
Section: Injerto Procedente De Donante En Asistoliaunclassified
“…Until a few months ago, the use of intestinal grafts from DCD donors was banned due to the false paradigm that susceptibility to ischemia made the clinical use of these organs unfeasible. Preclinical (16) and clinical (17) evidence recently demonstrated that multivisceral grafting from DCD donors with normothermic perfusion can be used safely in patients. However, the indications and limitations of the use of these organs remain to be defined.…”
Section: Graft From Dcd (Donor After Cardiac Death) Donorsmentioning
confidence: 99%
“…However, the use of DCD as a source of intestinal grafts has been denied through years due to concerns about ischemic susceptibility [8]. The experimental studies that support this point of view are limited and involve heterogeneous methodologies and currently, it is contrasted with updated experimental evidence that shows DCD as promising in the field of intestinal and multivisceral transplantation [9,10]. In addition, the clinical evidence supporting the use of these grafts in the clinical setting is promising but scant [11,12].…”
Section: Introductionmentioning
confidence: 99%